Aprofundar a compreensão leitora em português l2 no nível avançado à luz do QECRL partindo do teste cloze - Lopes, Ângela Filipe; Martins, Fernanda; Pinto, Maria da Graça L. Castro (Linguarum Arena, 2015)
This study aimed at comparing the performance of an experimental group composed of advanced Portuguese L2 learners and a norm group of native speakers of Portuguese on a reading task. Using the Cloze test as a comparison instrument between both groups, the study was based on the analysis of existing L2 reading research literature and the references provided by the CEFR in order to design a set of seven two hour lessons focusing on deep reading press columns featuring literary, complex and hybrid characteristics. The results showed that the performance of the experimental group were distant not only from those of the norm group but also from the illustrative descriptors of the CEFR for C1 and C2 proficiency levels. Research on the field of language learning methods and strategies was necessary in order to design reading activities that would enable the students to deepen reading comprehension. The second phase of testing leads to the conclusion that, with this group of subjects, the methodological choices implemented throughout the reading lessons that were held between both testing moments led to an improvement in reading processing.